The Problems in Kaiwa Learning Faced by Students - Mardhatillah, D P; Setiana, S M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aimed to describe the problems faced by students in learning Kaiwa and how the efforts of lecturers to overcome the problems. The research design was action research. The data were taken through a questionnaire to the students and documentation studies. The respondents in this study are 54 students of 1st grade of the Japanese Department at Universitas Komputer Indonesia for the academic year 2022/2023. The results showed that the problems that occur when learning Kaiwa are a lack of student motivation, limited learning resources, lack of variety of teaching methods, lack of opportunities to speak with native speakers, lack of language skills, and a less conducive learning environment. These problems can be addressed using various teaching techniques such as role-playing, interviews, extensive reading, retaining Kaiwa learning, and incorporating material that has been studied into the learning management system provided by the university so that students can see the material and can study it anywhere and anytime. Improving the quality of Kaiwa learning by using various approaches, methods, and learning media are urgently needed.